Histological characterization of Passiflora pohlii Mast. root tips cryopreserved using the V-Cryo-plate technique - Simão, Mariela J.; Collin, Myriam; Garcia, Renata O.; Mansur, Elisabeth; Pacheco, Georgia; Engelmann, Florent (Protoplasma, 2018)
Cryopreservation stands out as the main strategy to ensure safe and cost efficient long-term conservation of plant germplasm, especially for biotechnological materials. However, the injuries associated with the procedure may result in structural damage and low recovery rates after cooling. Histological analysis provides useful information on the effects of osmotic dehydration, LN exposure, and recovery conditions on cellular integrity and tissue organization, allowing the determination of the critical steps of the cryopreservation protocol and, thus, the use of optimized treatments. Passiflora pohlii Mast. (Passifloraceae) is a native species from Brazil with potential agronomic interest. Recent studies showed the presence of saponins in its roots, which presented antioxidant activity. The goal of this work was to develop a cryopreservation technique for root tips of in vitro-derived plants of P. pohlii using the V-Cryo-plate technique and to characterize the anatomical alterations that occurred during the successive steps of the protocol. Root tips were excised from in vitro plants and precultured before adhesion to cryo-plates and then treated for different periods with the plant vitrification solutions PVS2 or PVS3. Treatment with PVS2 for 45 min resulted in higher recovery (79%) when compared with PVS3 (43%). The greatest number of adventitious roots per cryopreserved explant was also observed after a 45-min exposure to PVS2. Plasmolysis levels were higher in cortical cells of cryopreserved explants treated with PVS2, while pericycle and central cylinder cells were not damaged after this treatment. Thirty days after rewarming, no plasmolysis could be detected, regardless of the experimental conditions.